2017
DOI: 10.1039/c6cc06475b
|View full text |Cite
|
Sign up to set email alerts
|

Beyond methylammonium lead iodide: prospects for the emergent field of ns2containing solar absorbers

Abstract: The field of photovoltaics is undergoing a surge of interest following the recent discovery of the lead hybrid perovskites as a remarkably efficient class of solar absorber. Of these, methylammonium lead iodide (MAPI) has garnered significant attention due to its record breaking efficiencies, however, there are growing concerns surrounding its long-term stability. Many of the excellent properties seen in hybrid perovskites are thought to derive from the 6s electronic configuration of lead, a configuration seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
360
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(363 citation statements)
references
References 456 publications
(195 reference statements)
3
360
0
Order By: Relevance
“…[11,13,15] However, devices based on these materials have low reported power conversion efficiencies under AM 1.5G illumination, between 0.1 and 1.2%. [1] The short-circuit current densities (J SC , <4 mA cm −2 ) and external quantum efficiencies (EQEs, <60%) have also been poor, [1,18] in spite of efforts to extend the photoconversion range of bismuth halide semiconductors (J SC < 3.4 mA cm −2 , EQE < 25%). [14] Although higher efficiencies have been reported in bismuth-and antimony-based chalcogenides, [19][20][21][22] it is important to understand whether the broader range of ns 2 compounds predicted to be defect-tolerant could also exceed 1% power conversion efficiency and reach the levels needed for commercial production after optimization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11,13,15] However, devices based on these materials have low reported power conversion efficiencies under AM 1.5G illumination, between 0.1 and 1.2%. [1] The short-circuit current densities (J SC , <4 mA cm −2 ) and external quantum efficiencies (EQEs, <60%) have also been poor, [1,18] in spite of efforts to extend the photoconversion range of bismuth halide semiconductors (J SC < 3.4 mA cm −2 , EQE < 25%). [14] Although higher efficiencies have been reported in bismuth-and antimony-based chalcogenides, [19][20][21][22] it is important to understand whether the broader range of ns 2 compounds predicted to be defect-tolerant could also exceed 1% power conversion efficiency and reach the levels needed for commercial production after optimization.…”
mentioning
confidence: 99%
“…[34] The absorption coefficients are on the order of 10 4 cm −1 (Figure 1c), which are on par with other indirect-bandgap solar absorbers. [1] To evaluate the transport properties of our CVT BiOI films, we measured their lifetimes by TCSPC. The PL decays were fluence-independent and exhibited initial bowing, followed by a tail with a slower decay.…”
mentioning
confidence: 99%
“…Historically, bulk V-VI-VII compounds attracted tremendous interest in the 1960s due to promising ferroelectric properties. [21][22][23][24][25][26] The last 5 years have witnessed the renaissance of these materials for photovoltaic applications beyond perovskites, [27][28][29][30][31][32][33][34] because (i) orienting crystal growth perpendicular to the substrate sustains excellent carrier transport along the chains, (ii) benign grain boundaries parallel to the chains are free of dangling bonds and hence cause little recombination loss, [35] and (iii) needle-like crystals aligned in the translational direction of the growth exhibit better photovoltaic response than their higher dimensional counterparts. [36] For applications in field-effect transistors, the Achilles' heel of bulk V-VI-VII semiconductors is smaller band gap, lighter effective mass, and much higher dielectric constant than 2D MoS 2 , [2,17,29,32] which seriously reduces their potential.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts are well-documented in recent reviews, and the compounds are compositionally analogous to lead-halide perovskites, e.g., methylammonium tin iodide, methylammonium germanium iodide, and methylammonium bismuth iodide. [8][9][10][11] Another strong emphasis has been on finding compounds with the same crystal structure, resulting in numerous investigations into double perovskites, e.g., Cs 2 AgBiBr 6 , which is also well-documented in recent reviews and articles. 8,[12][13][14] An approach that is contemporary to these is to find compounds that could replicate the tolerance of lead-halide perovskites to intrinsic defects.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Another strong emphasis has been on finding compounds with the same crystal structure, resulting in numerous investigations into double perovskites, e.g., Cs 2 AgBiBr 6 , which is also well-documented in recent reviews and articles. 8,[12][13][14] An approach that is contemporary to these is to find compounds that could replicate the tolerance of lead-halide perovskites to intrinsic defects. Computations of methylammonium lead iodide (CH 3 NH 3 PbI 3 ) have shown that it primarily forms shallow defects, which would lead to low rates of Shockley-Read-Hall recombination.…”
Section: Introductionmentioning
confidence: 99%